2010
DOI: 10.1111/j.1365-2966.2010.16240.x
|View full text |Cite
|
Sign up to set email alerts
|

The rotational structure of methanol and its excitation by helium

Abstract: We have extended and improved previous calculations of cross-sections for the rotational excitation by helium of A-and E-type methanol in their torsional ground states. We increased the maximum value of the rotational quantum number, j, of the methanol molecule from j = 9, used in the previous calculations, to j = 15, thereby ensuring the completeness of the rotational energy levels and the corresponding basis of eigenfunctions up to the first threshold for exciting the internal torsional motion of the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The fitted species are listed in the order plotted in Table 2. Note that A-and E-type methanol can only interchange in chemical reactions, but barring peculiar excitation processes, they should be governed by the same partition function (Rabli & Flower 2010).…”
Section: Temperatures and Columns In The Hot Coresmentioning
confidence: 99%
“…The fitted species are listed in the order plotted in Table 2. Note that A-and E-type methanol can only interchange in chemical reactions, but barring peculiar excitation processes, they should be governed by the same partition function (Rabli & Flower 2010).…”
Section: Temperatures and Columns In The Hot Coresmentioning
confidence: 99%
“…On the other hand, the collisional transitions connecting 0 0,0 to the lower 1 1,1 and 2 1,2 states have rate coefficients that are set to zero in the present E-CH 3 OH/p-H 2 data set (Rabli & Flower 2010a). As discussed in Rabli & Flower (2010b), this is an artefact of the coupled state (CS) approximation used in the production of the collision cross sections, and it is very likely that the collisional 0 0,0 −1 1,1 and 0 0,0 −2 1,2 transitions actually have small, but non-zero, rate coefficients. Repeated tests using altered sets of collisional data showed that rate coefficients as small as 3 × 10 −11 cm 3 s −1 (ca.…”
Section: Non-lte Modellingmentioning
confidence: 99%
“…The first group used the state of the art effective Hamiltonian [91], which included 120 fitting parameters. The second group used a much simpler model [95]. The rotational part H rot was that of the slightly asymmetric top and included the rotational constants A, B, and C (A ≈ B).…”
Section: Molecules With Hindered Rotation: Methanol and Methylaminementioning
confidence: 99%